Estimation of transaction costs on Bursa Malaysia = Anggaran kos urus niaga di Bursa Malaysia - Puteh, Nor Shazlenna; Abdullah, Mimi Hafizah; Abdullah, Lili Marziana (2014)
Estimation of transaction costs in stock market is an important issue for stock trading, asset pricing, and stock market regulation etc. and it is often done by combining the quoted bid-ask spread estimate with commissions and other fees provided by market participants which can be subjective. The main objective of this study is to estimate the transaction costs in stock trading on Bursa Malaysia. Even though there are many studies that have been conducted in estimating transaction costs in stock trading on other countries stock exchange, as to date, there is no similar study for the Malaysian stock exchange. This research aims to estimate the transaction costs used by the market for the selling and buying of an asset on the Bursa Malaysia for the year 2013 using daily stock market returns for a sample of top 30 stocks. This study also determines a better estimator of transaction costs which can cover all its components. The more components of transaction costs included in the estimation, the better is the estimation of transaction costs. In this study, Roll’s model and Corwin and Schultz’s (CS) model are used to estimate transaction costs. Since Roll’s model only measures bid-ask spread which is only one of the components of transaction costs, the CS measure is shown to be a better estimator because it covers bid-ask spread as well as liquidity costs. Thus, a benchmark of transaction costs estimation in stock trading on the Bursa Malaysia is determined and can be used as a guide for investors when they want to participate in Malaysia’s stock trading.